Clinical potential of lixisenatide once daily treatment for type 2 diabetes mellitus - Petersen AB (Dove Medical Press, 2013)
Andreas B Petersen,1 Mikkel Christensen1,21Department of Clinical Pharmacology, Bispebjerg Hospital, Copenhagen, Denmark; 2Diabetes Research Division, Department of Internal Medicine, Gentofte Hospital, Copenhagen, DenmarkAbstract: The glucagon-like peptide (GLP)-1 receptor agonist lixisenatide (Lyxumia®) was approved for marketing by the European Medicines Agency in February 2013 and has been evaluated in a clinical study program called GetGoal. Lixisenatide activates the GLP-1 receptor and thereby exercises the range of physiological effects generated by GLP-1, which consist of increased insulin secretion, inhibition of glucagon secretion, and decreased gastrointestinal motility alongside the promotion of satiety. In the GetGoal study program, lixisenatide demonstrated significant reductions in glycated hemoglobin (HbA1c), and fasting and postprandial plasma glucose compared with placebo. The effect on glycemia was evident, with both monotherapy and in combination with insulin and various oral antidiabetic agents. Furthermore, a general trend towards reduced bodyweight was reported. In head-to-head trials with the other GLP-1 receptor agonists (exenatide and liraglutide) on the market, lixisenatide demonstrated a superior effect with respect to reduction in postprandial plasma glucose and had a tendency towards fewer adverse events. However, lixisenatide seemed to be less efficient or at best, equivalent to exenatide and liraglutide in reducing HbA1c, fasting plasma glucose, and bodyweight. The combination of a substantial effect on postprandial plasma glucose and a labeling with once daily administration separates lixisenatide from the other GLP-1 receptor agonists. The combination of basal insulin, having a lowering effect on fasting plasma glucose, and lixisenatide, curtailing the postprandial glucose excursions, makes sense from a clinical point of view. Not surprisingly, lixisenatide is undergoing clinical development as a combination product with insulin glargine (Lantus®). At present the main place in therapy of lixisenatide seems to be in combination with basal insulin. A large multicenter study will determine the future potential of lixisenatide in preventing cardiovascular events and mortality, in patients with type 2 diabetes and recent acute coronary syndrome.Keywords: GLP-1, incretin, pharmacology, GetGoal, T2DM